Comparison of static and dynamic exposures to air pollution, noise, and greenness among seniors living in compact-city environments - Oriol Marquet; Jose Tello-Barsocchini; Daniel Couto-Trigo; Irene Gómez-Varo; Monika Maciejewska (International Journal of Health Geographics, 2023)
Highlights Static and dynamic exposures were estimated for a set of basic exposures (NO2, PM2.5, PM10, dB, NDVI) among 113 seniors in Barcelona. Static exposures were based on residential location while 7-day GPS tracking was used for dynamic exposures. Dynamic assessments using GPS-tracking are not providing enough accuracy across all the range of exposures. PM2.5, and noise exposures significantly benefited from GPS-tracking use. NO2, PM10, and exposures to greenness did not lose significant accuracy using only residential static exposures with Barcelona’s seniors